A study on halloysite reinforced chitosan hydrogel nanocomposites: synthesis, characterization & DYE adsorption properties - Palantöken, Sinem. (Thesis (M.S.) - Bogazici University. Institute for Graduate Studies in Science and Engineering, 2015., 2015)
In this project, synthesis and characterization of a series of natural silica nanotube reinforced chitosan nanocomposite hydrogels are done. Nanocomposite hydrogels were prepared through physical crosslinking of chitosan and within different percentages of Halloysite nanotube (HNTs) reinforcement. To increase the surface activity of halloysite nanotubes without disturbing the tubular structure, a special modification based on cryoscopic expansion was conducted and modification success was confirmed by X-Ray Diffraction, Brunauer-Emmett-Teller and Scanning Electron Microscope analysis methods. It has been found that both inner and outer diameters as well as surface area of nanotubes can be increased efficiently without disturbing the inherent tubular structure. Hydrogel nanocomposites were then prepared with different percentages of original and modified halloysite nanotubes and their water absorption, mechanical and dye adsorption properties as well as morphologies were investigated with a special focus on lumen modification and loading degree. Compared to neat hydrogels, swelling and mechanical properties of the composite hydrogels were found to be enhanced because of special morphology devolopment depending on composition. This effect was observed in a distinct way when cryo-expanded halloysite nanotubes were considered. Besides that neat chitosan turns out to be a good adsorbent for anionic dye; if small amount of cryo-expanded halloysite is added into the composition, the resultant composite hydrogel displays not only high adsorption capacity for both anionic and cationic type of dyes but also better mechanical properties.
Keywords: Colloids.; Nanocomposites (Materials)